A comprehensive study on image segmentation - maruthi nagendra prasad, J.; M.VamsiKrishna, Dr. (International Journal of Engineering and Technology, 2018)
With the evolution of computing, there is an acceleration in the use of image processing techniques in various applications, image segmentation, a procedure in which images are divided into many segments and with this, it’s possible to identify the region of interest from an image. The main idea of this comprehensive study is to present various existing segmentation techniques.